Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1063/1.4841015
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the hydrogen content on the photoluminescence efficiency of amorphous silicon alloys

Abstract: This paper analyzes the impact of hydrogen on the photoluminescence (PL) efficiency of the three wide gap silicon alloys: silicon carbide (a-SiCx), silicon nitride (a-SiNx): silicon oxide (a-SiOx). All three materials behave similarly. The progression of the PL efficiency over the Si content splits into two regions. With decreasing Si content, the PL efficiency increases until a maximum is reached. With a further decrease of the Si content, the PL efficiency declines again. A comprehensive analysis of the samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…From the principles of planar geometry optics, we know that the emitted photons generated inside the samples are partially influenced by total internal reflection, and most of the generated photons are trapped inside the samples, since the refractive index of a-SiN x O y samples ( n ) is much higher than the air index (nair). Thus, the first part of light extraction factor N1 can be calculated as [26,27]:N1[1(nnairn+nair)2]×12(11(nairn)2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the principles of planar geometry optics, we know that the emitted photons generated inside the samples are partially influenced by total internal reflection, and most of the generated photons are trapped inside the samples, since the refractive index of a-SiN x O y samples ( n ) is much higher than the air index (nair). Thus, the first part of light extraction factor N1 can be calculated as [26,27]:N1[1(nnairn+nair)2]×12(11(nairn)2).…”
Section: Resultsmentioning
confidence: 99%
“…The remaining photons inside the sample should directly stroke or be internally reflected onto the rough substrate surface, which can also be scattered in all directions, and then emit out from the top surface [26,27], thus contributing the second and third parts of the light extraction factor N2 and N3, respectively. The rest of the contributions were too weak to separate out, and should be ignored.…”
Section: Resultsmentioning
confidence: 99%
“…In 2000, Pavesi et al first reported on the nc-Si optical gain and stimulated emission at room temperature, and it is expected to become an efficient luminescent material [ 6 ]. Obtaining more suitable Si-based luminescent materials and improving the related fluorescence quantum efficiency has been one of the most difficult tasks in this field for more than two decades [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%